The Relationship Among Road Traffic Accidents Population Size and the Number of Motor Vehicles in Turkey - Aşırdizer, Mahmut; Uluçay, Tarık; Hekimoğlu, Yavuz; Yılmaz, İlknur; Yavuz, Mehmet Sunay (The Bulletin of Legal Medicine, 2014)
Introduction: Traffic accidents with high morbidity and mortality rates are one of the most important problems of the world. Several factors have been described for the occurrence of traffic accidents. Two of them are traffic congestion and road density which have infrequently been reported in the Turkish literature. In this study, it was aimed to evaluate the relationship between road traffic accidents, population size, and the number of motor vehicles in Turkey.Material and methods: The crude data were obtained from the web page of the Turkish Statistical Institute. They was standardized for every one million population, every one million motor vehicles, or every one thousand road traffic accidents. The system of Statistical Regions was used in the classification.Results: In Turkey, the total number of inhabitants was 74,724,269 and the number of motor vehicles was 16,089,528 in 2011. As a result of 131,845 road traffic accidents 3,835 people died and 238,074 people were injured. In the evaluation of  the distribution of the number of motor vehicles for every one million population, the distribution of the number of road traffic accidents for every one million population and every one million motor vehicles,  the distribution of the number of people died in road traffic accidents for every one million population, every one million motor vehicles and every one thousand road traffic accidents, and the distribution of the number of people injured in road traffic accidents for every one million population, every one million motor vehicles and every one thousand road traffic accidents were all statistically significant. Conclusion: In the traffic accidents, urban and rural society based projects for the identification of risk factors and the preventive measures are great importance. This study represents a pioneer step forward in this field in Turkey.Keywords: Road traffic accidents, traffic congestion, road density, number of motor vehicles, population.
Keywords: road traffic accidents; traffic congestion; road density; number of motor vehicles; population